IMF Staff Papers, Volume 52, No. 1. (IMF Staff Papers; IMF Staff Papers ;, 2005)
This first issue of IMF Staff Papers for 2005 contains 7 papers that discuss: whether output recovered after the Asian crisis; the value of a country's trading partners to its own economic growth; whether interdependence is a factor in understanding the spread of currency crises; can remittance payments from expatriates be a reliable source of capital for economic development?; total factor productivity; designing a VAT for the energy trade in Russia and Ukraine; and lastly, a discussion of the reasons for central bank intervention in ERM-I since 1993.